2014
DOI: 10.1093/bja/aeu319
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pressure above the upper cerebral autoregulation limit during cardiopulmonary bypass is associated with postoperative delirium

Abstract: clinicaltrials.gov NCT00769691 and NCT00981474.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 34 publications
6
123
2
3
Order By: Relevance
“…Previous studies among coronary artery bypass graft patients have also shown that intraoperative cerebral perfusion pressure changes exceeding the limits of cerebral autoregulation dramatically increase the risk of postoperative delirium (23). For example, Hori and colleagues (23) found that the presence of delirium was fourfold higher among coronary artery bypass graft patients whose MAP levels exceeded the upper limit of autoregulation capacity during surgery (13% vs. 3%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies among coronary artery bypass graft patients have also shown that intraoperative cerebral perfusion pressure changes exceeding the limits of cerebral autoregulation dramatically increase the risk of postoperative delirium (23). For example, Hori and colleagues (23) found that the presence of delirium was fourfold higher among coronary artery bypass graft patients whose MAP levels exceeded the upper limit of autoregulation capacity during surgery (13% vs. 3%) (23).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Patients were eligible for enrolment if they were judged to be at high risk for stroke, as we have previously described. [8][9][10][11] Patients were excluded if they did not speak English, if they had visual impairment, or if there were contraindications to magnetic resonance imaging. The relationship between urine flow rate and MAP values below the lower limit of CBF autoregulation using this database has not been reported.…”
Section: Methodsmentioning
confidence: 99%
“…12 A continuous, moving Pearson's correlation coefficient between MAP and TCD blood flow velocity signals was then calculated to generate the variable mean velocity index (Mx). [8][9][10][11][12] When MAP is outside the limits of CBF autoregulation, Mx approaches 1, whereas it is close to 0 or negative when MAP is within the limits of autoregulation.…”
Section: Transcranial Doppler-based Autoregulation Monitoringmentioning
confidence: 99%
See 2 more Smart Citations